When conceptual autonomy leads to in the (autonomous) absence: Where is moral damage going? A revision of Italian case law - Oliveri, Luca (2021)
ABSTRACTThe starting point of this brief itinerary within the jurisprudence of legitimacy is constituted by the famoussentences of San Martino, pronounced by the United Sections in November 2008, a true and proper crucial moment concerning the subject matter of attention. If this is the starting point, it is not yet possible, on the other hand, to identify a real moment of conclusion of this path, since the point of arrival, far from being reached, looks more and more like a mirage. However, within this ( secular ) litaniae sanctorum, one may sometimes come across some statements that could be peacefully defined as unexpected, if not surprising: small deviations, in short, from the usual path of argumentation that struggle to fit into the latter in a logically coherent way, generating not a little confusion in the jurist. KEYWORD:jurisprudence, theory of law, damages, morality, justice RESUMENEl punto de partida de este breve itinerario dentro de la jurisprudencia de la legitimidad está constituidopor las famosas sentencias de San Martino, pronunciadas por las Secciones Unidas en noviembre de 2008, un verdadero y propio momento crucial con respecto al tema que nos ocupa. Si este es el punto de partida, todavía no es posible, por otra parte, identificar un momento real de conclusión de este camino, ya que el punto de llegada, lejos de ser alcanzado, se parece cada vez más a un espejismo. Sin embargo, dentro deestos litaniae sanctorum (seculares), uno puede encontrarse a veces con algunas afirmaciones que podrían definirse tranquilamente como inesperadas, cuando no sorprendentes: pequeñas desviaciones, en definitiva, de la senda habitual de la argumentación que pugnan por encajar en ésta de forma lógicamente coherente, generando confusión en el jurista. CÓDIGO JEL: K41, K12